Promoting Women’s Empowerment (SDG): An Attempt to Visibilise, Influence and Modify Gender Inequality on Instagram - García Gómez, Antonio (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2021)
The present paper acts on the commitment that the 21st-century university has made to the development of the Agenda 2030. more precisely, this paper describes in detail an innovation Project developed at the university of Alcalá that conceptualises the student as an active social agent. After reviewing the 17 sustainable Development Goals (SDGs) that the Agenda 2030 comprises, the four main phases the Project consists of are explained. By completing these four phases, the project aims to engage second year students in the Degree on modern languages and translation to apply all the content and competences they had acquired during the course in the design of memes and advertisements that promote gender equality. in so doing, they are not only encouraged to raise awareness of gender bias in society but also to take the initiative to fight against gender inequalities. Given that the students were required to post their work on the social networks, they could contribute actively to the visibility of this social injustice. the results highlight strengths and weaknesses. on the one hand, this project has had a positive impact on the student motivation and the student learning. on the other hand, the limited scope of the initiative has underscored one of the main avenues for improvement that may result in future studies.